Obesity and Breast Cancer: Current Insights on the Role of Fatty Acids and Lipid Metabolism in Promoting Breast Cancer Growth and Progression - Blücher, Christina; Stadler, Sonja C. (Frontiers in Endocrinology, 2017)
ABSTRACT Obesity and excess accumulation of adipose tissue are known risk factors for several types of cancer, including breast cancer. With the incidence of obesity constantly rising worldwide, understanding the molecular details of the interaction between adipose tissue and breast tumors, the most common tumors in women, becomes an urgent task. In terms of lipid metabolism, most of the studies conducted so far focused on upregulated de novo lipid synthesis in cancer cells. More recently, the use of extracellular lipids as source of energy came into focus. Especially in obesity, associated dysfunctional adipose tissue releases increased amounts of fatty acids, but also dietary lipids can be involved in promoting tumor growth and progression. In addition, it was shown that breast cancer cells and adipocytes, which are a major component of the stroma of breast tumors, are able to directly interact with each other. Breast cancer cells and adjacent adipocytes exchange molecules like growth factors, chemokines and interleukins in a reciproke manner. Moreover, it was shown that breast cancer cells can access and utilize fatty acids produced by neighbouring adipocytes. Thus adipocytes, and especially hypertrophic adipocytes, can act as providers of lipids, which can be used as a source of energy for fatty acid oxidation and as building blocks for tumor cell growth.